Psycholinguistic analysis of lexical-semantic structure in linguistic consciousness of Russian, English and German native speakers - Victoria Sibul (Peoples' Friendship University of Russia (RUDN University), 2017)
The study examines lexical-semantic structures in the linguistic consciousness of an individual and considers the factors affecting the establishment of these structures. Understanding the way people categorise the outer world is essential for the development of cross-cultural communication skills. The study analyses linguistic consciousness studies in the field of linguistics, psychology and psycholinguistics and provides findings of research into internal structure of a semantic field 'bird' in the linguistic consciousness of Russian, English, and German speakers. The findings will be interesting to specialists in intercultural communication and foreign language teachers. The methodological framework is based on the psychometric ranking of verbal and non-verbal stimuli followed by statistical data processing implemented to reveal the nature of results correlation. These results were further exposed to comparative analysis to define the factors bringing about both similarities and discrepancies. The analysis helped prove that both linguistic and cultural phenomena affect the position of a component within a semantic field, making up its core and periphery. Linguistic phenomena feature symbolism, metaphorisation, and word-formation, while cultural phenomena are represented by geographic location and practical skills of communication.